'A more perfect arrangement of plants': the botanical model in psychiatric nosology, 1676 to the present day. Issue 2 (June 2018) - Mason, Daniel; Hsin, Honor
Psychiatric classification remains a complex endeavour; since the Enlightenment, nosologists have made use of various models and metaphors to describe their systems. Here we present the most common model, botanical taxonomy, and trace its history from the nosologies of Sydenham, Sauvages and Linnaeus; to evolutionary models; to the later contributions of Hughlings-Jackson, Kraepelin and Jaspers. Over time, there has been a shift from explicit attempts to pattern disease classification on botanical systems, to a more metaphorical use. We find that changes in the understanding of plants and plant relationships parallel changes in the conceptualization of mental illness. Not only have scientific discoveries influenced the use of metaphor, but the language of metaphor has also both illuminated and constrained psychiatric nosology.